Detection of Norovirus in Saliva Samples from Acute Gastroenteritis Cases and Asymptomatic Subjects: Association with Age and Higher Shedding in Stool - Anfruns-Estrada, Eduard; Sabrià, Aurora; Fuentes, Cristina; Sabaté, Sara; Razquin, Efrén; Cornejo, Thais; Bartolomé, Rosa; Torner, Nuria; Izquierdo, Conchita; Soldevila, Nuria; Coronas, Lorena; Dominguez, Angela; et al. (Viruses, 2020)
Norovirus infections are a leading cause of acute gastroenteritis outbreaks worldwide and across all age groups, with two main genogroups (GI and GII) infecting humans. The aim of our study was to investigate the occurrence of norovirus in saliva samples from individuals involved in outbreaks of acute gastroenteritis in closed and semiclosed institutions, and its relationship with the virus strain, virus shedding in stool, the occurrence of symptoms, age, and the secretor status of the individual. Epidemiological and clinical information was gathered from norovirus outbreaks occurring in Catalonia, Spain during 2017–2018, and stool and saliva samples were collected from affected and exposed resident individuals and workers. A total of 347 saliva specimens from 25 outbreaks were analyzed. Further, 84% of individuals also provided a paired stool sample. For GII infections, norovirus was detected in 17.9% of saliva samples from symptomatic cases and 5.2% of asymptomatic individuals. Positivity in saliva occurred in both secretors and nonsecretors. None of the individuals infected by norovirus GI was positive for the virus in saliva. Saliva positivity did not correlate with any of the studied symptoms but did correlate with age ≥ 65 years old. Individuals who were positive in saliva showed higher levels of virus shedding in stool. Mean viral load in positive saliva was 3.16 ± 1.08 log10 genome copies/mL, and the predominance of encapsidated genomes was confirmed by propidium monoazide (PMA)xx-viability RTqPCR assay. The detection of norovirus in saliva raises the possibility of oral-to-oral norovirus transmission during the symptomatic phase and, although to a lesser extent, even in cases of asymptomatic infections.